Kepastian Hukum Pasca Pencabutan Perkara Perbankan Syariah (Studi kasus No. 04/Pdt.Eks/2024/PA.Sdn) - Lita Permana Juniati; Aziza Aziz Rahmaningsih (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2026)
The withdrawal of a case in a sharia banking dispute raises legal issues related to legal certainty and protection for the parties, especially when the withdrawal is carried out without a court decision or peace deed. This research examines legal certainty after the withdrawal of sharia banking cases through case study No. 04/Pdt.Eks/2024/PA.Sdn at the Sukadana Religious Court. This case started with a customer's default in mudharabah and musyarakah contract-based financing, which resulted in the filing of a request for execution by a sharia bank, but was later withdrawn due to an out-of-court settlement. Normatively, Articles 271-272 HIR provide the right to withdraw cases, but do not strictly regulate the legal consequences after revocation, thereby creating a vacuum of norms and legal uncertainty regarding the legal position of the parties. This research uses a normative juridical method with an empirical normative juridical approach, supported by primary and secondary data. The research results show that the withdrawal of the case returns the parties to their original state (status quo ante) without executive certainty. This condition causes the loss of legal basis for creditors to carry out execution if the debtor defaults again. Apart from that, the revocation reflects the absence of norms in civil procedural law and weakens legal protection for creditors in resolving sharia banking disputes.